Experimental and numerical investigation of hydrothermal effect on mechanical properties of adhesively bonded T-joint - Siti Nurhashima Mohd Isa (School of Mechatronic Engineering, 2016)
In this study, the hydrothermal effect on epoxy adhesive with variable bond thickness is investigated in parametric studies. The material in this study involves stainless steel 304 containing two parts, namely stainless steel plate with dimension of 100mm X 100mm X 10mm and stainless steel perforated plate with dimension of 100mm X 80mm X 1.25mm. This specimens are made from actual 1.25mm perforated plate to simulate the actual structure of fluidisation bed in PCFK granulator equipment. Araldite epoxy adhesive was used in this study.The specimen is exposed into two conditions, room temperature and dry (RTD) and elevated water temperature (EWT) for bulk adhesive specimen and T-joint specimen. Besides that, the experiments are conducted in the room temperature for both bulk adhesive and T-joint specimens subjected to axial loading; compression and tensile. The thickness of adhesive and temperature of water are considered as parameters in this investigation. The thickness was varied as 0.5mm, 1.0mm, 1.5mm and 2.0mm, while aging condition at water temperatures of 80°C, 90°C and 100°C were used in this study.